2013
DOI: 10.1111/dgd.12033
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a retinoic acid‐responsive neural enhancer in the Ciona intestinalis Hox1 gene

Abstract: The Hox1 gene in the urochordate ascidian Ciona intestinalis (Ci-Hox1) is expressed in the nerve cord and epidermis. We identified a nerve cord enhancer in the second intron of Ci-Hox1, and demonstrated that retinoic acid (RA) plays a major role in activating this enhancer. The enhancer contained a putative retinoic acidresponse element (RARE). Mutation of the RARE in the Ci-Hox1 nerve cord enhancer only partially abolished the enhancer activity. Genes encoding RA synthase and the RA receptor were knocked down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The conservation of ParaHox gene expression in the CNS allows us to dissect ParaHox regulation in Ciona , as the CNS of Ciona shows clear similarities in gene expression to the wider Chordata, perhaps even the Bilateria [ 66 , 67 ]. In addition, the tunicates also retain many of the signalling pathways involved in Hox and ParaHox regulation, such as RA [ 68 70 ], FGF [ 71 73 ], BMP [ 74 , 75 ], Wnts [ 76 , 77 ] and hedgehog [ 76 , 78 , 79 ]. By using C. intestinalis , we are able to quickly assess hundreds of embryos at a time, allowing the identification of even weak regulatory elements, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of ParaHox gene expression in the CNS allows us to dissect ParaHox regulation in Ciona , as the CNS of Ciona shows clear similarities in gene expression to the wider Chordata, perhaps even the Bilateria [ 66 , 67 ]. In addition, the tunicates also retain many of the signalling pathways involved in Hox and ParaHox regulation, such as RA [ 68 70 ], FGF [ 71 73 ], BMP [ 74 , 75 ], Wnts [ 76 , 77 ] and hedgehog [ 76 , 78 , 79 ]. By using C. intestinalis , we are able to quickly assess hundreds of embryos at a time, allowing the identification of even weak regulatory elements, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cis ‐regulatory assays of mouse hindbrain enhancers in Ciona and Ciona Hox regulatory modules in mouse and chick embryos revealed that enhancers dependent upon and capable of reading out input from segmental regulators such as Krox20 and Kreisler are specific to the vertebrate lineage . Hox genes are up‐regulated upon RA treatment in Ciona embryos but RA appears to have a less profound influence on neural Hox expression in tunicates than in vertebrates, which is possibly linked to Hox cluster disintegration …”
Section: Insights From Invertebrate Chordates Into the Evolution Of Tmentioning
confidence: 97%
“…Only a modest number of regulatory elements are identifiable by sequence conservation between tunicates and vertebrates (reviewed in), but comprehensive regulatory surveys of Ciona Hox loci have uncovered a number of enhancer sequences . For example, two enhancers proximal to ci‐Hox1 have been implicated in its neural and ectodermal expression, which contain RAREs that may be homologues of those in amphioxus and vertebrate Hox clusters.…”
Section: Insights From Invertebrate Chordates Into the Evolution Of Tmentioning
confidence: 99%
“…). The identification of RA‐responsive Hox enhancers in a urochordate provides further support for this scenario .…”
Section: Insights Into the Evolution Of The Hindbrain Grn From Invertmentioning
confidence: 99%